Social media monitoring by personnel in libraries: listening etiquette and best practices for engaging users (2023)
Social media has the ability to build social Capital, facilitate knowledge sharing, and be used for internal and external communication by institutions and organizations. Many libraries around the world, on the other hand, appear to sign up for and make their presence known on various social media platforms without actively using them. Perhaps there isn’t enough manpower to keep track of how libraries use social media to give Services to their patrons. Asa result, this study discussed concerns related to social media surveillance by library workers as well as effective practices for interacting and listening to users. The paper was written using a literature- based methodology. Textbooks, scholarly publications, media, and Internet sources were used to compile the literature review, which encompassed the years 2007 to 2017. Before valid decisions for inferences were made, issues and themes were thoroughly compared. Best practices for engaging library users on social media; Social media monitoring plan for library Professionals; Building some early social media successes; Measuring the efficiency of social media strategies; The lead generation funnel; Best practices for engaging library users on social media; and Listening etiquette for engaging library users on social media were all reviewed thoroughly. Facebook, Linkedln, MySpace, Academia.com, GoodRead.com, Classmates.Com, LibraryThing, YouTube, Instagram, Podcast, Pinterest, Flicker, Tumblr, and other social media platforms were deemed useful for effective, dependable, and satisfactory Information and Service delivery to users. Consequently, library marketing strategies should be improved to ensure that patrons of individual libraries are adequately informed about web-based Information resources and Services available, as well as where such resources and services could be offered to them on Internet-related platforms, particularly social media. Library management should also provide regular training and workshops for library staff and users in Order to improve their ICT literacy.